2010
DOI: 10.1161/circulationaha.109.926808
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Models for Prolonged Intensive Care Unit Stay After Cardiac Surgery

Abstract: Background-Several models have been developed to predict prolonged stay in the intensive care unit (ICU) after cardiac surgery. However, no extensive quantitative validation of these models has yet been conducted. This study sought to identify and validate existing prediction models for prolonged ICU length of stay after cardiac surgery. Methods and Results-After a systematic review of the literature, the identified models were applied on a large registry database comprising 11 395 cardiac surgical interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
1
10

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 53 publications
5
99
1
10
Order By: Relevance
“…With respect to the outcome measures ICU LOS and hospital LOS, our study confirms previous findings [5,26]: Ettema and associates validated several prediction models for prolonged ICU stay after cardiac surgery and found that both Parsonnet score and EuroSCORE had superior discrimination compared to other predictive scores [27]. Interestingly, both models widely implemented in clinical practice, were originally derived and validated only for the prediction of mortality after cardiac surgery.…”
Section: Discussionsupporting
confidence: 86%
“…With respect to the outcome measures ICU LOS and hospital LOS, our study confirms previous findings [5,26]: Ettema and associates validated several prediction models for prolonged ICU stay after cardiac surgery and found that both Parsonnet score and EuroSCORE had superior discrimination compared to other predictive scores [27]. Interestingly, both models widely implemented in clinical practice, were originally derived and validated only for the prediction of mortality after cardiac surgery.…”
Section: Discussionsupporting
confidence: 86%
“…24,25 While some features of the EuroSCORE had to be estimated in our population, composite metrics reduce the risk of a type 1 error compared with including individual characteristics. EuroSCORE is a significant predictor of other adverse outcomes in cardiac surgical patients, including prolonged ICU length of stay 26 and mortality, both in a large multicenter population 27 and in a population from our institution. 28 While the association between ASA PS and postoperative delirium has been better studied in noncardiac surgical populations, 29,30 it is not surprising that ASA PS is related to postoperative delirium in this cardiothoracic surgical population as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ettema et al [5] performed an external validation of 14 risk scores capable to identify patients who are likely to have a prolonged ICU stay. The Parsonnet model and the EuroSCORE showed the best performance in terms of discrimination, accuracy, and calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Those scores have been successfully validated also for prediction of prolonged LOSI. Parsonnet model and EuroSCORE were superior in identifying patients with prolonged LOSI [5].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation